Instrumentation of an optical fiber probe for online detection of bacteria in water - Lin, Yishan. (2009)
The detection of pathogenic bacteria is key to the prevention and identification of problems related to health and safety. Legislation is particularly tough in areas such as the water industry, where failure to detect an infection may have terrible consequences. In spite of the real need for obtaining an analytical result in the shortest time possible, traditional and standard bacterial detection methods may take up to 7 or 8 days and some even take up to weeks. The advent of new technologies, namely biosensor, has brought in new and promising approaches. However much research and development work is still needed before biosensors become a real and trustworthy alternative. This research report provides an investigation and a theoretical review of detecting online bacteria through the instrumentation of an optical fiber probe a kind of biosensor. The report begins with a description of its background, purpose and scope. Next, it provides theoretical background on the equipments and items that are used in the experiments. The experiments determined that the detection of fluorescence in glass slides and fibers sample was not positive and positive if cuvette samples were used.